Sustainable urban development of mobility and streetscape in historic city quarters, an ancient street in Alexandria - Egypt, as a case study - Ola Hassan; Eman A.K. Mohamed; Aly Hassan; Magdy Shaheen; Wael Bekheet (Alexandria Engineering Journal, 2023)
A historic urban district is a quarter built many years ago and contains valuable memories over a limited area with narrow streets for pedestrians, primitive transportation, and outdoor activities. Over the years, many districts have been growing randomly, and motorized transport has enlarged significantly and created severe problems. Improving the situation needs heritage protection and sustainable mobility development on its streets. The desired mobility focuses on managing travel demands, accessibility for all street users, and enhancing the environment. This research presents a proposed approach with an application framework for sustainable mobility development on historic roads according to its current conditions at the strategic level. It includes sequential phases to define desired goals, formulate and evaluate planning scenarios containing different action measures based on sustainability indicators and application of micro-simulation. In case of inappropriate evaluation results, approach phases allow the modification and re-evaluation of additional measures until deciding an acceptable solution. The application is limited to Ras El-Teen Palace Street, prominent in the ancient El Gomrok district, Alexandria and restricted to a Do-Nothing solution and a planning scenario. The application proves the approach's practicality and feasibility by improving traffic behaviour. Furthermore, the planning approach can indicate technical recommendations for further improvement.